RANCANG BANGUN VERTICAL LAMINER AIR FLOW CABINET (LAFC) DILENGKAPI DUAL SYSTEM CONTROL: Design Vertical Laminer Air Flow Cabinet (LAFC) Equipped with Dual Control System - ST. MT. Kusnadi (Politeknik Unggulan Kalimantan, 2024)
Lafc played an important role in achieving optimal results in the process of inoculation of bacteria, preparation of media, preparation of spore suspensions, dilution of bacterial samples, and multiplication of bacteria. This studied aims to created a lafc tool that had development in the form of modifying controlled systems and monitoring cabinet temperature and humidity. The typed of researched used was quantitative researched and the researched method was researched and development (RnD), with steps consisting of preliminary studied, product design, design validation, design revision, product trials, and expert validation. The results of product testing from data in the field could been summarized as follows. The voltage generated by the power supply was 12.2 Vdc with an error valued of 0.2 and an error accuracy of 1.6%. In the Exhaust Fan test, the average measured voltage was 222.7 Vac with an error valued of 2.7 and an error accuracy of 1.22%. In the DC Fan test, the average measured voltage was 12.2 vdc with an error valued of 0. 2 and an error accuracy of 1. 6%. In the DHT22 sensor test, the sensor accuracy values obtained for temperature measurements was 99.49% and for humidity measurements was 99.89%. In the dual system-controlled test used a timer, the average measurement time for setting during the sterilization process was 30 minutes 2 seconds.